Alpha chemicals limited - Ochieng', Peter (My University, 2013)
The timing of this Stocks control system project appears to be opportune, since many upcoming organizations tend to run manual stocking and re-stocking systems which hinders the performance, and objectives are rarely met as there is no control of goods coming in and moving out, valuation of such goods is also not possible, it is therefore currently a subject of significant concern to the business industry. With this in mind, I have come up with a system which may address, highlight and solve some if not all of such problems. The project/program have been reviewed and run and I trust that it will provide an invaluable resource. Apart from the computer hardware and the peripherals and an operating system, no other particular equipment are recommended